English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i got a certain answer but it's incorrect and i can't seem to get the correct answer. can anybody pls. explain... thank you

2007-03-19 19:21:10 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

6(9x^2-7x+1)^5 (18x-7) is the answer

2007-03-19 19:24:20 · answer #1 · answered by fckstanfurd 2 · 0 0

F(x)=(9x^2-7x+1)^6
F'(x)=6(9x^2-7x+1)^5*(18x-7)

2007-03-19 19:24:23 · answer #2 · answered by yupchagee 7 · 0 0

it is just a power formula...
1. bring down 6 of the exponent of the whole term
2. then differentiate the inside term so it would be 18X-7
3. less one from the original exponent so 6-1=5
4. so the expression would be 6(9X^2-7X+1)^5(18X-7)
5. then for you to expand or leave it that way

2007-03-19 19:43:27 · answer #3 · answered by Dylan 1 · 0 0

F(x) = (9x^2 - 7x + 1)^6
F'(x) = 6(18x - 7)(9x^2 - 7x + 1)^5

2007-03-19 19:36:15 · answer #4 · answered by Helmut 7 · 0 0

f(x) = g(h(x))
f'(x) = g'(h(x))*h'(x)
f(x) = (9x^2-7x+1)^6
f'(x) = 6(9x^2-7x+1)^5*(18x-7)

That was *way* too easy.

Doug

2007-03-19 19:28:01 · answer #5 · answered by doug_donaghue 7 · 0 0

Chain Rule: initiate on the exterior and artwork your way in. View e^(3x^2) as e^u the place u = 3x^2 is a few functionality of x spinoff of e^u = e^u * u'(x) exterior then interior u'(x) = 6x dy/dx = 6x*e^(3x^2) + 7

2016-12-19 09:28:11 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers